2009
DOI: 10.1089/gtmb.2009.0045
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms in Genes Encoding Toll-Like Receptor -2, -3, -4, and -9 in Case–Control Study with Breast Cancer

Abstract: These results suggest that polymorphisms in tested TLR genes are not likely to be associated with increased risk for developing breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 58 publications
2
41
2
1
Order By: Relevance
“…In agreement with these findings, Etokebe et al (34) failed to demonstrate any correlation between the TLR2 d allele and breast cancer development. However, a study by Theodoropoulos et al (35) reported a positive association between this polymorphism and an increased risk of breast cancer in the Greek population.…”
Section: Discussionmentioning
confidence: 58%
“…In agreement with these findings, Etokebe et al (34) failed to demonstrate any correlation between the TLR2 d allele and breast cancer development. However, a study by Theodoropoulos et al (35) reported a positive association between this polymorphism and an increased risk of breast cancer in the Greek population.…”
Section: Discussionmentioning
confidence: 58%
“…Despite the numerous data demonstrating alteration of TLR mRNA expression by ligand activation, few reports demonstrated the consequence or specific mechanism by which TLRs themselves are transcriptionally regulated. In addition, the importance of TLR transcriptional regulation is highlighted by the fact that several single nucleotide polymorphisms in TLR promoters predispose humans to several autoimmune and chronic inflammatory diseases, including asthma and Crohn's disease (44)(45)(46)(47)(48)(49)(50)(51). In this article, we provided novel insights on the transcriptional regulation of TLR9 with dsDNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no studies have demonstrated significant associations between this SNP and breast (Etokebe et al, 2009;Resler et al, 2013), bladder (Singh et al, 2013), prostate (Mandal et al, 2012), colorectal (Li et al, 2009), and cervical cancers (Pandey et al, 2011;Lai et al, 2013), except for one study, which reported an increased risk for cervical cancer (Roszak et al, 2012). Consistent with most of these individual studies, in this meta-analysis incorporating 11 case-control studies with 3775 cases and 3769 controls, we found no significant evidence supporting an association between cancer risk and the rs352140 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the titles, abstracts, and full texts of all retrieved articles through defined criteria. Finally, 19 articles were included in this study (Nieters et al, 2006;Etokebe et al, 2009;Hold et al, 2009;Mollaki et al, 2009;Ashton et al, 2010;Pandey et al, 2011;Zeng et al, 2011;Chen et al, 2012;Carvalho et al, 2012;Li et al, 2012;Mandal et al, 2012;Miedema et al, 2012;Noack et al, 2012;Roszak et al, 2012;Xie et al, 2012;Lai et al, 2013;Resler et al, 2013;Singh et al, 2013;. Since more than one case-control study was included in ten articles (Nieters et al, 2006;Hold et al, 2009;Mollaki et al, 2009;Ashton et al, 2010;Carvalho et al, 2012;Li et al, 2012;Miedema et al, 2012;Roszak et al, 2012;Lai et al, 2013;Resler et al, 2013), they were considered as separate studies in the meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%